Alteration of synonymous codon usage bias accompanies polyploidization in wheat - Tian, Geng; Xiao, Guilian; Wu, Tong; Zhou, Junzhi; Xu, Wenjing; Wang, Yanxia; Xia, Guangmin; Wang, Mengcheng (Frontiers in Genetics, 2022)
The diploidization of polyploid genomes is accompanied by genomic variation, including synonymous nucleotide substitutions that may lead to synonymous codon usage bias (SCUB). SCUB can mirror the evolutionary specialization of plants, but its effect on the formation of polyploidies is not well documented. We explored this issue here with hexaploid wheat and its progenitors. Synonymous codons (SCs) ending in either cytosine (NNC) or guanidine (NNG) were more frequent than those ending in either adenosine (NNA) or thymine (NNT), and the preference for NNC/G codons followed the increase in genome ploidy. The ratio between NNC/G and NNA/T codons gradually decreased in genes with more introns, and the difference in this ratio between wheat and its progenitors diminished with increasing ploidy. SCUB frequencies were heterogeneous among exons, and the bias preferred to NNA/T in more internal exons, especially for genes with more exons; while the preference did not appear to associate with ploidy. The SCUB alteration of the progenitors was different during the formation of hexaploid wheat, so that SCUB was the homogeneous among A, B and D subgenomes. DNA methylation-mediated conversion from cytosine to thymine weakened following the increase of genome ploidy, coinciding with the stronger bias for NNC/G SCs in the genome as a function of ploidy, suggesting that SCUB contributes to epigenetic variation in hexaploid wheat. The patterns in SCUB mirrored the formation of hexaploid wheat, which provides new insight into genome shock-induced genetic variation during polyploidization. SCs representing non-neutral synonymous mutations can be used for genetic dissection and improvement of agricultural traits of wheat and other polyploidies.